The impact of trademarks on small business enterprises' performance in Uzbekistan - Nasirillaeva Nadida (International Journal on Economics, Finance and Sustainable Development, 2021)
In a competitive environment, brands have become an increasingly effective marketing tool because they encourage clients to discern between original products and counterfeit products and take actions based on more factual information. This article examines the role of Trademarkson small business and private entrepreneurship enterprises’ performance in Uzbekistan and important aspects of its development.